Using digital footprint data to monitor human mobility and support rapid humanitarian responses. Issue 1 (31st December 2022) - Rowe, Francisco
ABSTRACT: Global warming is increasing the frequency of extreme weather events leading to an increased risk of large-scale population displacements. Since June 2022, Pakistan has recorded destructive flash flooding resulting from melting glaciers and torrential monsoon rainfall. Emergency responses have documented flood-related deaths, injuries and damaged infrastructure – less is known about population displacements resulting from recent floods. Information about these populations and mobility is critical to ensure the appropriate delivery of humanitarian assistance where it is most needed. Lack of granular spatial data in real time has been a key barrier. This article uses digital footprint data from Meta Facebook to identify the patterns of population displacement in Pakistan in near-real time.